Numerical study for the development of flood maps considering the break hypothesis in irrigation reservoirs - F.J. Sánchez-Romero; M. Pérez-Sánchez; M. Redón-Santafé; J.B. Torregrosa Soler; C. Ferrer Gisbert; J.J. Ferrán Gozálvez; A. Ferrer Gisbert; P.A. López-Jiménez (Ingeniería del Agua)
The need to regulate the water volume as a function of irrigation needs, as well as the availability of hydric resources, caused the building of a high number of irrigation reservoir. This research describes the process for the development of floods maps when the break hypothesis is considered in irrigation reservoirs. This process was applied on 14 study cases, using FLDWAV and IBER model. The results showed the difference between the failure forms (piping and overtopping). These differences force to consider the two failure hypotheses in the study. Different criteria of damage were defined through velocity and depth values, which enable to interpret more specific the risk areas. The study contributes to improve the interpretation of this type of situations, helping in the planning and management of these possible emergencies.